The Influence of Brand Trust, Brand Experience on Purchase Intention on the sustainability of the business cooperation of PT Burdah Unggul Sejahtera moderated by Service Quality - Lukiyana Lukiyana; Raisa Anjani (Budapest International Research and Critics University, 2022)
The development of the company in the global era requires PT Burdah Unggul Sejahtera (PT Bultera) to continue to pay attention to good company performance and totality to clients/business partners in order to have an impact on increasing business performance, return on investment (ROI), satisfaction, customer loyalty, profit, and demand for goods/services products as well as the sustainability of business cooperation in various sectors. The purpose of this study was to examine the effect of brand trust, brand experience on purchase intention moderated by service quality on the sustainability of business cooperation with PT Bultera. The research method used in testing this research variable is quantitative with the partial least square technique with a structural equation model (PLS-SEM) approach and assisted processing using SmartPLS 3 software (v.3.3.9). In collecting sample data, the researcher chose to use PT Bultera's internal and external census techniques, namely employees, business partners, and clients of 187 respondents to directly examine the influence between variables and variable moderation. The results in this study indicate that there is a significant influence of brand trust on purchase intention, there is a significant influence of brand experience on purchase intention, and there is a significant effect of service quality on purchase intention. Then the results of testing the moderating variable show that the influence of brand trust on purchase intention is significantly moderated by service quality. Meanwhile, service quality does not have a moderating effect on the relationship between brand experience and purchase intention.